The evolution of selector gene function: Expression dynamics and regulatory interactions of tiptop/teashirt across Arthropoda. Issue 6 (17th September 2018) - March, Logan E.; Smaby, Rachel M.; Setton, Emily V. W.; Sharma, Prashant P.
Abstract : The transcription factors spineless ( ss ) and tiptop/teashirt ( tio/tsh ) have been shown to be selectors of distal appendage identity in an insect, but it is unknown how they regulate one another. Here, we examined the regulatory relationships between these two determinants in the milkweed bug Oncopeltus faciatus, using maternal RNA interference (RNAi). We show that Ofas ‐ ss RNAi embryos bear distally transformed antennal buds with heterogeneous Ofas ‐ tio/tsh expression domains comparable to wild type legs. In the reciprocal experiment, Ofas ‐ tio/tsh RNAi embryos bear distally transformed walking limb buds with ectopic expression of Ofas‐ss in the distal leg primordia. These data suggest that Ofas‐ss is required for the maintenance of Ofas ‐ tio/tsh expression in the distal antenna, whereas Ofas ‐ tio/tsh represses Ofas ‐ ss in the leg primordia. To assess whether expression boundaries of tio/tsh are associated with the trunk region more generally, we surveyed the expression of one myriapod and two chelicerate tio/tsh homologs. Our expression survey suggests that tio/tsh could play a role in specifying distal appendage identity across Arthropoda, but Hox regulation of tio/tsh homologs has been evolutionarily labile.